Induced biochemical changes in Ganoderma boninense infected Elaeis guineensis seedlings in response to biocontrol treatments - Tuan Hassan, Tuan Muhammad Syafiq; Syd Ali, Nusaibah; Yusop, Mohd Rafii (Universiti Putra Malaysia, 2023)
Despite massive economic contributions to Malaysia, the oil palm industry faces devastating threats from basal stem rot (BSR) disease. An array of treatments was designed to evaluate the potential of biological control agents (BCAs) as a single and combination of applications in a greenhouse study of six months. Oil palm enzymes, phenolic content, and metabolite induction in BSR-diseased seedlings were also assessed in response to the designed treatments. In the study, seedlings treated with Trichoderma asperellum (UPM16) demonstrated the highest disease reduction (DR) (57.2). Peroxidase (PO), lignin, and total phenolic content (TPC) were evaluated. Treatments on Ganoderma-infected seedlings treated with Bacillus cereus (UPM15) exhibited the highest reading in all assays. Gas chromatography-mass spectrometry (GC-MS) analysis profiled phenol, 4-2-aminoethyl-as the most abundant metabolite detected in combination treatments with B. cereus and T. asperellum (BT). Both BCAs complimented and demonstrated huge potential in mitigating BSR diseases in oil palm. However, excessive chemical application to control BSRs negatively impacts biodiversity and the human population. In view of this, studies on biological control are crucial in selecting potential BCAs to counter BSR sustainably. Biological control would be an ideal alternative as a sustainable method for controlling oil palm BSR disease.